A sub-threshold CMOS temperature sensor circuit core with 2.41 mV/°C sensitivity for ultra-low-power applications (-100°C to 100°C) - Abdelhakim Megueddem; Khaled Bekhouche (Indonesian Journal of Electrical Engineering and Computer Science, 2026)
This paper presents a sub-threshold complementary metal-oxide semiconductor (CMOS) temperature sensor core for ultra-low-power applications, with the key advantage of reliable operation over an exceptionally wide temperature range from –100 °C to 100 °C, which is rarely reported in existing CMOS-based designs. The proposed architecture operates entirely in the sub-threshold region and is evaluated using circuit level simulations, with validation through comparison to a previously reported temperature sensor. Simulation results show excellent linearity across the full temperature range, achieving a coefficient of determination of R² = 0.99997 and a sensitivity of approximately 2.41 mV/°C. At a supply voltage of 1.4 V and 25°C, the sensor core consumes only 22 nW, highlighting its suitability for energy-constrained applications. These results demonstrate the potential of sub-threshold CMOS temperature sensing for wide-range, ultra-low-power sensing systems.